Distribution System Nodal Prices Determination for Realistic ZIP and Seasonal Loads: An Optimal Power Flow Approach. (2016) - Polisetti, Karimulla; Kumar, Ashwani
Abstract: The impact of deregulation in power system has changed the electricity pricing scheme where the prices are governed by the rules of market operation. The prices must take into account the effect of load and must be based on the change in the operating state of the system. In this paper an optimal power flow approach is used to determine the marginal clearing price along with the nodal prices by minimizing the total system operation cost. The method uses marginal loss coefficients (MLCs) to get these prices, the results are compared with realistic ZIP, residential, industrial and commercial (RIC) load patterns which are also considered with seasonal variations such as winter, summer and spring seasons. The entire study is conducted on IEEE 33 bus radial distribution system (RDS) using GAMS 23.4 and the seasonal load is taken from IEEE Reliability Test System (RTS) data.